Factores que limitan la gestión de las políticas de desarrollo económico local en la municipalidad provincial de Abancay en el período 2007-2009 - Ramírez Atoche, Santos Guillermo (2012)
The present document constitutes the final research report of the thesis "Factors that limit the management of local economic development policies in the Provincial Municipality of Abancay in the period 2007-2009", to qualify for the Master's Degree in Management Social of the Catholic University of Peru (PUCP). The research aimed to identify the main factors preventing the managing authorities and officials of the Provincial Municipality of Abancay from implementing effectively policies to promote Local Economic Development (DEL) in the period 2007-2009, which corresponds to the current Mayoral management, understanding that the issue is at the level of attitudes and behavior of the actors involved and that they involve different interests to approach or engage in local government investigation focused their perceptions. The main theme focuses specifically on the observation and analysis of attitudes and behavior of the actors involved namely, the municipal authorities and officials. For this, the study had to investigate the perception of the authorities in relation to the potential of policies, assess the institutional capacities of the municipality for the design and implementation of policies for promotion of DEL, and explore the perceptions of local economic actors in relation to the role of the municipality in promoting DEL. The format of research that was chosen was the study case and the methodology was qualitative The investigation established that: First, between the municipal authorities there are different visions but not necessarily conflicting ones about the role of the municipality in promoting local economic development. Second, the municipal management takes place in a context of severe institutional limitations to complete their functions. Third, local economic actors do not have a clear idea of the role played by the municipality in promoting the economic development of the province of Abancay.